(untitled) (Eurasian Scientific Herald, 2025)
This article examines the phenomenon and vocal individuality of Maria Callas, one of the most influential opera singers of the twentieth century. Particular attention is given to the structure and expressive capacity of her vocal apparatus, which combined rare technical precision with profound emotional depth. The study analyses the features that shaped her distinctive timbre, interpretative originality, and the evolution of her performing style within the bel canto tradition. It also considers Callas’s professionalism, dramatic intuition, and ability to transform each operatic role into a psychologically convincing character. Her voice, capable of both lyrical delicacy and tragic intensity, redefined the expressive boundaries of the soprano repertoire. The article reflects on how Callas’s artistic legacy, marked by extraordinary talent and a deeply tragic fate, became an enduring manifestation of vocal genius in modern operatic art